Value Relevance of Accounting Information During IFRS Convergence Process In Indonesia - Tri Lestari; Tomomi Takada (The Indonesian Journal of Accounting Research, 2015)
Abstract: The purpose of this study is to examine the value relevance of accounting information in Indonesian market during the IFRS convergence process. Specifically, we investigate whether value relevance improves after significant revisions of standards during the period from 2005 to 2012. Using the price model and return model, we examine the accounting information value relevance of Indonesia listed firms. As predicted, we find that the value relevance of accounting information increases after the accounting standards change. We further document some determinants of value relevance, such as the less informativeness of negative earnings and the more value relevance both of large firms and firms with a higher level of good corporate governance before and after accounting standard change. Finally, these findings contribute to the ongoing debate of IFRS convergence effect on accounting quality, especially the case in emerging markets.Abstrak: Penelitian ini bertujuan untuk menguji relevansi nilai dari informasi akuntansi di pasar modal Indonesia selama proses konvergensi IFRS. Secara khusus, penelitian ini menginvestigasi adanya peningkatan relevansi nilai setelah adanya revisi standar akuntansi secara signifikan selama periode tahun 2005 sampai 2012. Dengan menggunakan price model dan return model, penelitian ini menguji relevansi nilai informasi akuntansi dari perusahaan-perusahaan yang terdaftar di Bursa Efek Indonesia. Sebagaimana telah diprediksi, penelitian ini menemukan bahwa relevansi nilai informasi akuntansi meningkat setelah perubahan standar akuntansi. Dari analasis tambahan, penelitian ini juga menemukan beberapa determinan relevansi nilai akuntansi yaitu laba positif vs laba negatif, ukuran perusahaan dan tingkat penerapan good corporate governance. Temuan dalam penelitian ini memberikan kontribusi pada isu tentang efek konvergensi IFRS pada kualitas informasi akuntansi yang masih menjadi perdebatan terutama untuk kasus pada pasar modal di negara sedang berkembang.